Pengaruh Kualitas Pelayanan terhadap Kepuasan Pengguna Jasa Bongkar Muat PT. Temas Shipping - Reishigano Megaputra, Hendyanta; Agus Setiono, Beni (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2021)
The best service form given the tematline that the company really appreciate the time owned by its customers. Therefore the Temasline’s commitment in terms of time on time is the added value that must be given to its customers. The sample in this study is a user service unloading service unloading at PT. Temas Shipping with quantitative research type and use descriptive approach. Using purposive sampling sampling method. The number of respondents participating in this study were 30 people. Methods and analysis using simple linear regression analysis to test the hypothesis. The results of the analysis showed an influence between service quality to satisfaction with the SIG level. 0.000 which <α (0.05) and r count = 13,5050 r table = 1.697. Correlation analysis shows the relationship of ministry positive effect on the user satisfaction with the SIG. 0.000 (<0.05) Rcount = 0,931 > R table = 0,931> R table = 0,391. After finding, the relation of strong relation of the relationship. Pearson Correlation value shows 0.931 means the relationship is very strong. Presentase influence of all independent variables on the dependent variable is 0.868. Meaning 86.8% Satisfaction of service users can be explained by the quality of service quality. While the remaining variables 13.2% influenced by other factors not studied in this study.